Caracterización Biofísica y Socioeconómica de las Zonas de Riego del cantón Catamayo, utilizando herramientas de la geomática. - Aguilar Hidalgo, Nicolás Alejandro (2023)
Field information was used to characterize the biophysical and socioeconomic aspects of the irrigation zones in the Catamayo canton, in order to identify land cover and soil use patterns. Spatial analysis techniques were also applied to evaluate the terrain characteristics and potential water resources in the study area. Furthermore, a socio-economic analysis was conducted which included surveys and interviews with local farmers to evaluate the productive structure and cultivation practices in the area. The results showed that the Catamayo canton has a wide variety of crops, including sugarcane, maize, tomato, and others. On the other hand, a great dependence on agriculture in the area was identified, which was reflected in the productive structure and distribution of cultivation lands. Regarding water resources, it was found that most of the irrigation zones are under water stress conditions, suggesting the need for better management of available resources. As for land cover, areas with potential for biodiversity conservation were identified, which could contribute to the sustainability of the agricultural system in the area. Keywords: Biophysical characterization, Soil use patterns, Spatial analysis, Water resources,irrigated areas